Dark Triad and Its Impact on Workplace Engagement, Turnover Intentions, Organisational Commitment Using Workplace Perceived Victimization and Manager–Employee Trust as Moderator - Vadiraja, Vinay (Digital Repository of Theses, 2026)
Dark Triad and its impact on work workplace engagement, turnover intentions, organizational commitment using workplace perceived victimization and manager-employee trust as moderator. Couple of decades ago, the idea of Dark Triad emerged with inclusion of 3 traits namely Machiavellianism, Narcissism, Psychopathy. Although these are undesirable traits, research has found that in certain circumstances these could deliver positive outcomes as well. This study aims to understand the influence of dark triad on subordinates when the dark triad traits are demonstrated by manager. The primary objective of the research is to comprehend the influence of Dark triad on organizational commitment and turn over intentions with work workplace engagement, workplace perceived victimization and manager employee trust as moderator. This study is seen through the lens of the following theories Psychological Contract Theory, Job Demand Resource Theory, Conservation of Resources Theory, and Leader-Member Exchange Theory. The study has deployed Descriptive Statistics, Linear Regression, Structural Equation Modeling (SEM), Confirmatory Factor Analysis (CFA) and Response Surface Method to arrive at the findings.